PENGARUH SARI KURMA TERHADAP LAMA PERSALINAN KALA I FASE AKTIF - Dian Aby Restanty; Miranda Apriliana; Susilawati (Ovary Midwifery Journal, 2023)
Prolonged first stage is one of the problems occurring in labor, this could happen caused by factors affecting labor such as mother’s power and uterine contractions (power). The worsening of uterine contraction is the main cause of labor distortion. Datas from Kemenkes by the year of 2018, show that 93,5% mothers experienced prolonged labor. This literature review study aims to identify effects of date fruit juice to the active phase of first stage of labor. This literature review study is a systematic mapping study. Articles analyzed were from databases, Google Scholar and Pubmed. 178 populations achieved from databases and screened using PICOS framework, 10 articles selected containing 5 international articles and 5 national articles. All of the articles state that there is effect of date fruit juice to active phase duration with p value <α (0,05). The duration of first stage of labor in the mothers who has given the date fruit juice is 2.55 minutes meanwhile in the control group the duration mean is 5.33 minutes. That from 10 articles, date fruit juice consumptions for 4 final weeks pregnancy and during labor has significantly effects and accelerate the duration of active phase of labor. It is hoped that health workers will provide information and knowledge for maternity mothers regarding the benefits of date palm juice which can help mothers to speed up the delivery process.